Place-Based Learning Through a Proxy - Variations in the Perceived Benefits of a Virtual Tour - Wallgrun, Jan Oliver; Knapp, Eric; Taylor, Alan; Klippel, Alexander; Zhao, Jiayan; Sajjadi, Pejman (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
Place-based and fieldwork learning play a key role in higher education in environmental sciences and other geospatial disciplines. We report on a study in which we evaluated a web-based virtual tour application for teaching natural resource management in fire-prone western forests in two undergraduate classes. The virtual tour uses 360°-image-based virtual scenes and pre-recorded audio commentary by a domain expert to lead participants through the Stanislaus-Tuolumne Experimental Forest where forest treatments were implemented to reduce fire hazard. We present results from assessing students' overall perception of the virtual tour, their views towards its application in undergraduate education, and their feedback for improving the design of future virtual tours. Furthermore, we discuss the collected data from the perspective of gender differences and differences in familiarity with the topic of the tour.